Greater Perceived Physical Fatigability Is Associated with Lower Cognition: The Long Life Family Study. (16th December 2020) - Gmelin, Theresa; Rosso, Andrea; Andersen, Stacy; Cosentino, Stephanie; Wojczynski, Mary; Christensen, Kaare; Boudreau, Robert; Glynn, Nancy
Abstract: Greater perceived physical fatigability is associated with physical functional decline, but few studies have examined its relation with cognition. Adults ≥60 (mean±SD age 73.7±10.5, 54.7% female, 99.6% white) from the Long Life Family Study (n=2355) completed the Pittsburgh Fatigability Scale (PFS, 0-50, higher=greater fatigability) and a neurocognitive examination. Generalized estimating equations were used to account for family structure. Covariates included age, sex, field center, depressive symptoms (Center for Epidemiological Studies-Depression), education, and self-reported health. Each 1-point greater PFS was associated with lower: (1) global cognition (Mini-Mental Status Exam; β=-0.36, p<.0001), (2) verbal fluency (phonemic: β=-0.09, p=.029 and semantic: β=-0.14, p<.0001), (3) memory (Hopkins Verbal Learning Test-Revised: β=-0.06, p=.037), and (4) psychomotor speed (Digit Symbol Substitution Test: β=-0.10, p<.0001), after covariate adjustment. Greater perceived physical fatigability was significantly associated with lower memory and cognitive function in older adults, and may represent a promising new biomarker of biological aging reflecting declining brain reserve, resilience, and neurodegeneration.